2017
DOI: 10.1103/physrevc.96.014905
|View full text |Cite
|
Sign up to set email alerts
|

Single electrons from heavy-flavor mesons in relativistic heavy-ion collisions

Abstract: We study the single electron spectra from D− and B−meson semileptonic decays in Au+Au collisions at √ sNN =200, 62.4, and 19.2 GeV by employing the parton-hadron-string dynamics (PHSD) transport approach that has been shown to reasonably describe the charm dynamics at RelativisticHeavy-Ion-Collider (RHIC) and Large-Hadron-Collider (LHC) energies on a microscopic level. In this approach the initial charm and bottom quarks are produced by using the PYTHIA event generator which is tuned to reproduce the fixed-ord… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 81 publications
2
12
0
Order By: Relevance
“…We recall that the PHSD approach has successfully described numerous experimental data in relativistic heavyion collisions from the Alternating Gradient Synchrotron (AGS), SPS, RHIC to LHC energies [30,33,[35][36][37]. More recently, the charm production and propagation has been explicitly implemented in the PHSD and detailed studies on the charm dynamics and hadronization/fragmention have been performed at top RHIC and LHC energies in comparison to the available data [38][39][40]. In the PHSD approach the initial charm and anticharm quarks are produced by using the PYTHIA event generator [41] which is tuned to the transverse momentum and rapidity distributions of charm and anticharm quarks from the Fixed-Order Next-to-Leading Logarithm (FONLL) calculations [42].…”
Section: Introductionmentioning
confidence: 99%
“…We recall that the PHSD approach has successfully described numerous experimental data in relativistic heavyion collisions from the Alternating Gradient Synchrotron (AGS), SPS, RHIC to LHC energies [30,33,[35][36][37]. More recently, the charm production and propagation has been explicitly implemented in the PHSD and detailed studies on the charm dynamics and hadronization/fragmention have been performed at top RHIC and LHC energies in comparison to the available data [38][39][40]. In the PHSD approach the initial charm and anticharm quarks are produced by using the PYTHIA event generator [41] which is tuned to the transverse momentum and rapidity distributions of charm and anticharm quarks from the Fixed-Order Next-to-Leading Logarithm (FONLL) calculations [42].…”
Section: Introductionmentioning
confidence: 99%
“…FIG. 2: Drag coefficient divided by the charm quark momentum (upper), q scaled by T 3 (middle), and the spatial diffusion coefficient (lower) of charm quarks as a function of temperature and/or charm quark momentum from the DQPM [22,23] in comparison with the spatial diffusion coefficients from lQCD calculations [31].…”
Section: B Transport Coefficientsmentioning
confidence: 99%
“…To describe the QGP we employ the dynamical quasiparticle model (DQPM) [21], where a QGP is composed of strongly interacting quasiparticles whose pole mass and spectral width are fitted to the equation-of-state obtained by lattice quantum chromodynamics (lQCD) calculation. The scattering between heavy quarks and the off-shell partons is calculated using leading order Feynman diagrams [22,23]. This is motivated by the fact that the DQPM reproduces the spatial diffusion coefficient of heavy quarks as a function of temperature, which is presently the only observable for heavy quarks from lQCD.…”
Section: Introductionmentioning
confidence: 99%
“…In literature several studies have been performed in these years, to study theoretically both these observables with the aim to understand heavy quark dynamics in QGP employing the Langevin or the on-shell Boltzmann transport equation [9,12,13,22,25,29,[35][36][37][38][39][40][41][42][43][44]. However, being the QGP strongly interacting, a full quantum description of the charm quark interaction should include in principle also the off-shell dynamics, an approach that has been developed only in [45] for the study of the transport coefficients and it is included in the PHSD approach to heavy-ion collisions [27,38,46]. Recently, it has been shown that also off-shell effects can play a role in the hadronization processes [47].…”
Section: Introductionmentioning
confidence: 99%